Relationship between the Pandemic Climate of Covid-19 and Leadership Styles on the Employees Performance of the Secretariat Regional on Kupang City Government - Jefirstson Richset Riwukore; Fellyanus Haba Ora; Luis Marnisah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of study was to analyze and prove the influence of the pandemic climate of Covid-19 and leadership style to employee performance. This research was conducted for three months, namely January-March 2022 at the Regional Secretariat of the Kupang City Government. This research is classified as quantitative research using methods of survey, confirmative, and verification. The research population was 1034 employees, the sampling was determined using the proportional stratified random sampling method with the Slovin technique, so that the research sample used was 288 employees. The types of data consist of primary and secondary data, which were obtained by techniques in questionnaire, observation, documentation, and interview. Data analysis used multiple linear regression using SPPS v 2.1 application. The results showed that the COVID-19 pandemic climate, either partially or simultaneously, had a positive and significant effect on performance, but leadership style had a negative and insignificant effect on employee performance. The coefficient of determination in this research was 83.7%.